2020
DOI: 10.1371/journal.pone.0235601
|View full text |Cite
|
Sign up to set email alerts
|

Female adolescents’ reproductive health decision-making capacity and contraceptive use in sub-Saharan Africa: What does the future hold?

Abstract: Introduction Given the social, economic, and health consequences of early parenthood, unintended pregnancy, and the risks of HIV infection and subsequent transmission, there is an urgent need to understand how adolescents make sexual and reproductive decisions regarding contraceptive use. This study sought to assess the association between female adolescents' reproductive health decision-making capacity and their contraceptive usage. Materials and methods Data was obtained from pooled current Demographic and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 50 publications
7
58
2
4
Order By: Relevance
“…Responses to this question were coded as "no method", "folkloric method", "traditional method" and "modern method". Details of the specific contraceptives under each of the methods have been described elsewhere [30]. The existing DHS variable excluded women who were pregnant and those who had never had sex.…”
Section: Definition Of Variables Outcome Variablementioning
confidence: 99%
“…Responses to this question were coded as "no method", "folkloric method", "traditional method" and "modern method". Details of the specific contraceptives under each of the methods have been described elsewhere [30]. The existing DHS variable excluded women who were pregnant and those who had never had sex.…”
Section: Definition Of Variables Outcome Variablementioning
confidence: 99%
“…Married adolescents and those who have had a child have been shown to be more likely to utilize modern contraceptives. Our study showed that contraceptive utilization in Zambia is lower than that of the sub-Saharan region average, Europe, Latin America and United States of America (USA) [9,10,[21][22][23] and higher than that in Uganda [17], Chad and Benin [9]. The higher prevalence in Europe and United States of America (USA) can be attributed to the easier access of contraceptives, increased funding of policies, and interventions being implemented by these governments compared to Zambia [22,24].…”
Section: Resultsmentioning
confidence: 58%
“…Promoting use of modern contraceptives in this age group is a priority intervention that will ensure improvement of pregnancy health-related outcomes [7,8]. Due to the heterogeneous nature of the sub-Saharan region, sub-regional variations exist in contraceptive use among young women [9]. Despite the various interventions and policies to promote modern contraceptives utilization among young women in Sub-Saharan Africa, the utilization rate has remained low [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the factors in uencing modern contraceptive utilisation among single mothers. The study differs from existing studies that focused on other segments of childbearing women such as adolescents [21][22][23], never married women [24][25][26] and women of advanced reproductive age [27][28][29][30] by focusing on single mothers. This group of women has received little attention in family planning programming in Nigeria.…”
Section: Discussionmentioning
confidence: 88%
“…Existing studies in Nigeria and elsewhere have examined the associated factors of modern contraceptive utilisation among different segments of women such as adolescents and young people [21][22][23], never married women [24][25][26], women of advanced reproductive age [27][28][29][30]. Other studies have focused the general population of childbearing women [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%